Preparation and Characterisation of Sago Starch-Graftpoly(Acrylic Acid) and Sago Starch-Graft Poly(Methylacrylate) - Yiam, Chong Bin (2001)
Acrylic acid and methyl acrylate were grafted onto sago starch by usjng potassium persulphate as an initiator under nitrogen gas atmosphere. The graft yield showed dependence on amount of initiator, amount of monomer, reaction temperature and reaction period. For sago starch-g-poly(acrylic acid), the optimum conditions were as follows: reaction temperature, 40°C; reaction period, 1.5 h; amount of initiator, 10 mmoles and amount of monomer, 0.0219 moles. However, for sago starch-gpoly( methyl acrylate), the optimum conditions obtained were reaction temperature, 50 °C; reaction period, 1.5 h; amount of initiator, 8.33 mmoles and amount of monomer, 0.087 moles. TGA studies showed that the grafted sago starches exhibit different thennal behavior as compared to sago starch. SEM micrographs showed that both acrylic acid and methyl acrylate were grafted homogeneously onto sago starch. The sorption capacity of sago starch-g-poly(acrylic acid) for Cu(II) was determined. The biodegradability study of the grafted copolymers was carried out by using a - amylase lipase. The results show that the maximum glucose produced for sago starch-gpoly( acrybc acid) was on the 2nd day of experiment. However. for sago starch-gpoly( metbyl acrylate). the maximum glucose produced was on the 3rd day. Swelling behavior of sago starch-g-poly(acrylic acid) in water and various salt solutions and sago starch-g-poly(methyl acrylate) in water and solvents were also investigated. The viscosity-average molecular weight increased with increase of poly(methyl acrylate) content in the graft copolymer. Sago starch-g-poly(methyl acrylate) has also been converted into poly(hydroxamic acid) chelating ion exchange resin using Candida Rugosa as a catalyst. The metal ion sorption rate of the resin produced based on Cu (II) at pH 3.5, was rapid. The metal ion separations of Fe(ID)-Cu(II), Fe(ID)-Cd(II), Fe(lll)Cr( iln. Fe(IIl)-Ni(II) and Fe(III)-Pb(II) were successfully carried out.